Prevalence of CYP2C9 and VKORC1 mutation in patients with valvular heart disease in Northern Thailand - Srun Kuanprasert (2018)
Background: Warfarin has been widely used for the prevention and treatment of thromboembolism. Warfarin therapy depends on interaction between physiological, environmental, and genetic factors. Vitamin K epoxide reductase (VKORC1) and cytochrome P450 2C9 (CYP2C9) enzyme conjointly determine the warfarin maintenance dose. The prevalence of CYP2C9 and VKORC1 variants varies among ethnic groups. The purpose of the present study was to investigate the prevalence of CYP2C and VKORC1 in the Northern Thai population. Material and Method: Patients with valvular heart disease who regularly took a steady maintenance warfarin dose for at least one month were recruited into the present study. Patients who had taken amiodarone or an anti-inflammatory drug were excluded. Clinical data were obtained from medical records. Five milliliters of whole blood was drawn from each patient for gene analysis and prothrombin time with international normalized ratio (INR) measurement. Results: From 242 patients, CYP2C9 *1/*1 was found in 230 patients (95%) and CYP2C9 *1/*3 was found in 12 patients (5%). Neither mutant CYP2C9*2 allele nor individuals homozygous for CYP2C9*3 were observed. Regarding VKORC1, haplotype AB was found in 83 patients (34.3%) and haplotype AA was found in 154 patients (63.6%). Haplotype BB (wild type) was found in five patients (2.1%). Conclusion: The prevalence of CYP2C9 *1/*1 is high while the prevalence of CYP2C9*2 and CYP2C9*3 is very low. VKORC1 haplotype AA is the most common among the Northern Thai population. Further study regarding pharmacogenetic and non-genetic factors to develop warfarin-dosing algorithm is warranted.